Profiles and curricula in sociology - Ruiz Restrepo, Jaime (La Sociología en sus Escenarios, 2009)
Abstract When we address the profile issue we are referring actually to two-bold aspects, though complementary. The first deals with the strict sense of the professional profile. That is to say, with the identity problem of the sociology, with the problem of its object, and with the context where it is registered as a social science. The academic training thus establishes some desirable characteristics and creates conditions within the training offered. Or rather, it defines areas of information, training and sensitization. The second aspect, on the other hand, is referred to the occupational profile. That is to say, to the conditional knowledge outlined by the productive rational to the development of that specific science and to its appropriation in the universities. In general terms, it refers to the characteristics wanted by the employer which at the time also conditions the inherent abilities and skills of the professional performance. In this sense we find, on one hand, that the University ought to tackle two commitment problems: with the social reality on the one side, and with the development of its scientific knowledge on the other. On the other hand, the University is facing a problem of personal and particular interests whose aim is to take a given knowledge, a "to know how to make" or job by part of the students. Resumen Al hablar de un perfil nos estamos refiriendo en realidad a dos aspectos audaces, aunque complementarios. El primero se refiere al sentido estricto del perfil profesional. Es decir, al problema de identidad de la sociología, al problema de su objeto, y el contexto en el que está registrada como una ciencia social. La formación académica por lo tanto, establece algunas características deseables y crea las condiciones dentro de la formación ofrecida. O más bien, que define las áreas de información, formación y sensibilización. El segundo aspecto, por otra parte, es a que se refiere el perfil profesional. Es decir, las condiciones esbozadas por el productivo racional para el desarrollo de una ciencia específica que a su crédito en las universidades. En términos generales, se refiere a las características buscadas por el empleador en el momento que también las condiciones de las capacidades y habilidades inherentes de la actuación profesional. En este sentido nos encontramos, por una parte, que la Universidad debe hacer frente a dos problemas, compromiso: con la realidad social, por un lado, y con el desarrollo de sus conocimientos científicos, por el otro. Por otra parte, la Universidad se enfrenta a un problema de personal y de los intereses particulares cuyo objetivo es tener un determinado conocimiento, un "saber hacer" o de puestos de trabajo por parte de los estudiantes.